COMPARISON OF COGNITIVE FUNCTION BETWEEN FIRST ISCHEMIC STROKE AND RECURRENT ISCHEMIC STROKE PATIENTS - Rizkia, Fildza Intan; Calista, Chandra; Gunadharma, Suryani; Hermawan, Asep Nugraha; Amalia, Lisda; Ong, Paulus Anam (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2022)
Background: Cognitive impairment is a common condition that may affect up to 50% of stroke patients. Post stroke cognitive impairment is associated with reduced quality of life, which may increase the number of dependency. Recurrent stroke may happen in approximately 25% patients and they have higher rates of cognitive impairment.Objective: The aim of this study is to examine the comparison of cognitive function between first ischemic stroke and recurrent ischemic stroke patients in Hasan Sadikin Hospital, Bandung.Methods: This study is a retrospective, cross-sectional study using the data recruited between the year 2012 - 2016 at the Department of Neurology at the Hasan Sadikin Hospital Bandung. The data collected in this study were demographic data, including age, level of education, and residence, and the clinical data as well. Cognitive function was assessed using Mini-Mental State Examination (MMSE). The comparison between the cognitive function between both groups were analyzed using the Mann-Whitney U test.Results: There were 428 subjects eligible for this study, with 207 subjects categorized as first ischemic stroke group and 221 subjects categorized as recurrent ischemic stroke group. There was a statistically significant difference in MMSE scores between the first ischemic stroke patients (24.90 Â± 4.64) and recurrent ischemic stroke patients (22.85 Â± 4.64 ) with a p value of 0.002.Conclusion: Recurrent ischemic stroke patients had lower MMSE scores than the first ischemic stroke patients. Clinicians should be more aware in detecting early cognitive impairment in stroke patients and in preventing the incidence of recurrent stroke.